2018
DOI: 10.1057/s41271-017-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

“It just forces hardship”: impacts of government financial penalties on non-vaccinating parents

Abstract: Despite strong evidence confirming vaccination is safe and effective, some parents choose not to vaccinate their children. In 2016, the Australian Government introduced legislation strengthening links between vaccination compliance and some government payments. We interviewed thirty-one non-vaccinating parents about the impacts of this policy. Data analysis produced three key themes: 'questioning policy integrity', 'minimising impact' and 'holding my ground'. Affected parents offset reduced income by removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 20 publications
6
68
0
Order By: Relevance
“…A further experimental study explored the tendency for individuals with a strong internal locus of control or self-trust to experience greater reactance to coercive messages, making them more susceptible to message fatigue 60. We observed similar results in an earlier analysis from this study where participants said that new government policies withholding financial benefits from non-vaccinating families made them more willing to engage in protest action 41…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A further experimental study explored the tendency for individuals with a strong internal locus of control or self-trust to experience greater reactance to coercive messages, making them more susceptible to message fatigue 60. We observed similar results in an earlier analysis from this study where participants said that new government policies withholding financial benefits from non-vaccinating families made them more willing to engage in protest action 41…”
Section: Discussionsupporting
confidence: 73%
“…A number of parents in this study who decided not to vaccinate in a climate of increasing policy pressure to do so, became more committed to their decision and to upholding their right to maintain autonomy in making health decisions for their family 41. The concept of ‘psychological reactance’, well established in the psychology literature,54 is defined by Steindl et al as ‘an unpleasant motivational arousal that emerges when people experience a threat to or loss of their free behaviours.…”
Section: Reactance To System Inflexibilitiesmentioning
confidence: 99%
“…In 2017, one of us (J.L.) was involved in a study that interviewed 31 parents in Australia who were refusing vaccination for their child 9 . Of this group, 17 indicated that they planned to get more involved in protest action if additional such measures were implemented, because they felt that the government was coercing them.…”
Section: Exemptions and Penaltiesmentioning
confidence: 99%
“…Financial incentives could work better than financial penalties. In line with this, Helps et al reported that financial penalties were not an effective policy measure for non-vaccinating families with an increased desire to maintain control over health choices for their children [43]. In fact, these parents were even found to accept income reductions by removing children from early childhood learning and accessing informal childcare arrangements.…”
Section: Initiatives Relating To Familiesmentioning
confidence: 99%